Simultaneous heat and mass transfer in sphere in presence of phase and chemical transformation under generalised boundary conditions - Tripathi G.; Shukla K.N.; Pandey R.N. (My University, 2025)
The present investigation includes a theoretical study of simultaneous heat and mass transfer in a sphere in presence of phase and chemical transformation. The transfer potentials are determined under the influence of most general type of boundary conditions. Approximate solutions of these transfer potentials have also been determined. The whole analysis has been presented in the dimensionless form with the help of similarity criteria. © 1975.